Entrepreneurial Motivation, Creativity, and Entrepreneurial Education on the Interest in Entrepreneurship of Generation Z Students with Self-Efficacy as A Mediating Variable - Nurisma, Dhea; Suhardi, Suhardi (Future Science, 2025)
This study aims to analyse the influence of entrepreneurial motivation, creativity, entrepreneurship education, and entrepreneurial experience on the entrepreneurial interest of Generation Z students, with self-efficacy as a mediating variable. Using a quantitative approach through a survey of 120 active students at universities in Bangka, the data were analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The results showed that creativity and entrepreneurship education had a positive and significant effect on self-efficacy and entrepreneurial interest. Entrepreneurial experience also contributes strongly to increasing self-efficacy, especially through practice-based activities such as business simulations, mentoring, and field studies. In addition, entrepreneurship education has been proven to have a significant direct influence on entrepreneurial interest, emphasising the importance of applied and contextual learning. Meanwhile, entrepreneurial motivation does not have a significant effect on self-efficacy, but it still has a positive influence on entrepreneurial interest. Mediation analysis reveals that self-efficacy acts as an important mediator that strengthens the influence of motivation, creativity, education, and entrepreneurial experience on entrepreneurial interest. These findings confirm that self-confidence is the main foundation in the formation of entrepreneurial intention. Overall, this study emphasises the importance of synergy between internal factors and experience-based education to encourage the growth of a confident young generation ready to enter the world of entrepreneurship.